PENGARUH PIJAT KAKI TERHADAP PENURUNAN TEKANAN DARAH PADA IBU HAMIL DENGAN HIPERTENSI DI RS YOGYAKARTA - Mawarti, Retno; Zaidah, Lailatuz (Universitas Jenderal Achmad Yani Yogyakarta, 2019)
Background: Hypertension in pregnancy is a disease that gets attention given the negative effects it has on both the mother and the fetus. Hypertension in pregnancy if not treated properly will develop into superimposed Preeclampsia along with the increase in gestational age. Massage with aromatherapy oil is a non-pharmacological therapy to reduce and maintain blood pressure in a range that can be tolerated by the body. Objective: This study aims to determine the effect of a foot massage with lavender essential oil on reducing blood pressure in pregnant women with hypertension. Methods: The methodology used in this study was pre-experimental with the control group. Respondents consist of 15 pregnant women with hypertension who had been given blood pressure-lowering therapy, 8 people performed foot massage and 7 people made the control with accidental sampling technique. Massage with lavender essential oil conducted for 15-20 minutes every day for 7 days. Data were obtained by measuring blood pressure before and after the intervention, and then recorded into the observation sheet. The control group performed pressure measurements before and after given by blood pressure-lowering drugs, then analyzed by descriptive and bivariate statistical tests. Results: The results showed that the blood pressure difference before and after systole intervention was 6,52, diastole 0.82 in the control group of blood pressure difference before and after being given systole drug 7,902 diastole 4,847 Paired t-test results in the systole intervention group 0.340, diastole 0.40 and in the systole control group 0.068, diastole 0.137 (p = 0.05). Conclusion: The conclusion is the effect of a foot massage with lavender essential oil in pregnant women with hypertension. Suggestions for pregnant women with primary hypertension should do foot massage to help lower blood pressure. Keywords: Aromatherapy, foot massage,hipertension, lavender, pregnancy.